Fitzmorris Run, Mount Industry, St. Thomas in the Vale (1845)
A Plan of Fitzmorris Run, Mount Industry, St. Thomas in the Vale the property of William Titley. Surveyed by John M. Smith, 1845.
Estate Map
NLJCols20082021
Keywords: Fitzmorris Run; Fitzmorris Run, Mount Industry, St. Thomas in the Vale